Influence of clay content and salinity on the bioavailability and toxicity of metals (copper and zinc) to soil organisms - Owojori, Olugbenga J. (Olugbenga John) (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Botany and Zoology))—University of Stellenbosch, 2009.